Abdominal tumors in children: A comprehensive study on the diagnosis, management, and clinical outcome of pediatric patients with lymphoma in Kashmir - Akhtar, Zahida; Kaleem, Zahid; Kakroo, Showkat Majeed (Asian Journal of Medical Sciences, 2022)
Background: Although primary abdominal tumors are rare but their diagnosis, high-cost treatment and psychological instability among both patients and parents are challenging. There are several types of abdominal tumors in pediatric age group which include neuroblastoma, Wilm’s tumor, hepatoblastoma, lymphomas, soft-tissue sarcomas, and germ cell tumors. Aims and Objectives: The present study was objectively conducted to identify Hodgkin lymphoma (HL) and non-Hodgkin lymphoma (NHL) tumors among all patients presented with abdominal tumors. In addition to this, histopatological profile, clinical profile and disease prognosis among such patients has also been analyzed. Materials and Methods: A total of 64 pediatric patients presented with primary abdominal tumors were included in the study but only 20 patients with lymphoma were identified. The study was conducted at the Department of Pediatric Division, SMHS Hospital Srinagar with effect from 2005 to 2008. Results: The Majority of NHL patients were found to have Stage II and Stage IV. Moreover, all the four cases of Hodkins lymphoma had Stage IV. Out of the 20 patients with lymphoma six died, of them five had NHL and one patient had HL, thus placing the overall survival rate as 70%. Conclusion: The present study demonstrated that both NHL and HL tumors may develop to advanced stage and even patient may die if the timely diagnosis and proper management is not there. We recommend collective team work of medicos from various departments for the precise diagnosis and optimal management of such patients.